(untitled) (REVISTA POIÉSIS, 2019)
This article offers a theoretical reflection and practical proposals from the HeterotRópico artistic laboratory, a nomadic laboratory - where we are investigating dance, performance, physical theater, in conjunction with other diverse social technologies. They bring tools to activate collective practices developed within open creative processes. We will focus on the seminar lab I have proposed at the Masters in Arts Practice and Visual Culture 2018-2019 in Madrid, bringing together an intercultural group of artists and thinkers of around practices of trans-disciplinary arts. Artistic laboratories, in the diverse formats that they are defined today, aim to activate a field of subjectivities and corporeality, explored and co-produced in their uniqueness during the artistic process.